FIBROCALCULOUS PANCREATIC DIABETES IN INDONESIA: A CASE SERIES - Loe, Luse; Seotedjo, Nanny NM; Permana, Hikmat (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Fibrocalculous pancreatic diabetes (FCPD) is a rare form of secondary diabetes that is related to malnutrition and low socioeconomic status. We would like to report this case series with FCPD in Hasan Sadikin Hospital. CASE In the first case, a 30-year-old female came with loss of consciousness, abdominal pain, and steatorrhoea. She has history of low birth weight and underweight (BMI 17.9). She was later diagnosed with diabetic ketoacidosis, anemia and severe malnutrition. Second case, a 31-yearold female came with malaise, weight loss, and dysuria. She has history of giving birth to a large baby and underweight (BMI 15.8). She was diagnosed with severe dehydration, urinary tract infection, acute kidney injury and malnutrition. Third case, a 24-year-old male came with abdominal pain, chronic diarrhea and weight loss. He was underweight (BMI 16.9). He was diagnosed with dehydration, anemia and thrombocytosis. Fourth case is a 46-year-old female with normal weight who was admitted to hospital due to relapsing abdominal pain. Fifth case, a male 24-year-old came with decreased consciousness, dyspnea, cough, headache, orbital pain and weight loss. He was later diagnosed with diabetic ketoacidosis, pneumonia, mycosis of the lungs, non arteritic anterior ischemic optic neuropathy, acute kidney injury, severe malnutrition, and anemia. In all patients we found calcification in the pancreas on plain xray of the abdomen. CONCLUSION FCPD should be included as a differential diagnosis of diabetes among the young in Indonesia. We recommend to check plain xray of the abdomen in young patients with diabetes.